Using chromatogram averaging to improve quantitation of minor impurities - Zawatzky, Kerstin; Lin, Mingxiang; Schafer, Wes; Mao, Bing; Trapp, Oliver; Welch, Christopher J. (Journal of chromatography, 2016)
Averaging of chromatograms can lead to enhancement of signal to noise ratio (S/N) in proportion to the square root of the number of measurements. Although the general principle has been known for decades, chromatogram averaging is almost never used in current pharmaceutical research. In this study we explore the utility of this approach, showing it to be a simple and easily accessible method for boosting sensitivity for quantification of minor components and trace impurities, where current techniques deliver insufficient S/N.
Gesehen am 01.10.2021